On the determinants of trade openness in low- and lower-middle-income countries in Africa: How important is economic growth? - Dennis Boahene Osei; Yakubu Awudu Sare; Muazu Ibrahim (Future Business Journal, 2019)
The existing literature highlights the determinants of trade openness with disregard to the income classifications of countries in examining whether the determinants differ given their income levels. This study, therefore, re-examines the drivers of trade openness in Africa relying on panel data with special focus on the role of economic growth. More specifically, we perform a comparative analysis of the factors influencing trade openness for low-income and lower-middle-income countries using the system generalized method of moments. Our findings suggest that, while economic growth robustly enhances openness in low-income countries, in the case of lower-middle-income countries, the impact is not robust and largely negative suggesting that higher growth is associated with less openness. We also find that, economic growth-openness nexus for the lower-income countries exhibits non-linearities and inverted U-shaped relationship in particular. Thus, while increases in real GDP per capita enhance openness, beyond an estimated threshold point, any increases in economic growth dampen openness. We discuss key implications for policy.
Keywords: 650; Trade openness; Economic growth; Low-income countries; Lower-middle-income countries; GMM; Africa